A History of Modern Art Painting, Sculpture, Architecture, Photography. - ARNASAN, H.H. (Thames & Hudson, 1988)
The Prehistory of Modern Art.nrealism and ImpresionismnPost-Impressionism.nOrigins of Modern ArchitecturenArt Nouveau.nThe Origins of Modern SculpturenFauvismnExpressionism in GermanynCubismnSurrealism